Valuing groundwater in a productive aquifer using the production function approach the case of rice production in Lumban, Laguna, Philippines - Quilloy, Antonio Jesus A. (Journal of Economics, Management & Agricultural Development, 2018)
Establishment of the price of groundwater is necessary step in designing means for its sustainable management in rice production. There are several techniques that can be used in groundwater valuation. It is important to identify a valuation method that is appropriate to existing natural conditions within which the groundwater is situated. This paper aims to estimate the value of groundwater in a productive aquifer that is located in Lumban, Laguna, Philippines. Based on an estimated rice production function, the paper revealed that the value of groundwater extracted for rice production is approximately PhP 1.13 per m3. Out of this estimated economic value, resource rent is roughly 66% while the remainder covers the financial cost associated with groundwater extraction.